HUBUNGAN TINGKAT PENGETAHUAN SEKS PRANIKAH DENGAN SIKAP REMAJA TENTANG PERILAKU SEKS PRANIKAH PADA SISWI KELAS X SMK ABDI NEGARA MUNTILAN TAHUN 2014 - Zuria Heksa Setya Rini; Esti Handayani (JURNAL KEBIDANAN, 2016)
Backround.This research is motivated by indication of sexsuality behavior in adolescent, although the rate still under 5 percent. There are 0,5 percent girls has had sexual intercourse for the first time is in 8, and 0,1 percent for boys. Contraceptive used is very limited at the time of sexual intercourse, 23.4 percent of boys and only 5.3 percent in girls.Purpose. The aim of study is to describe the level of knowledge and attitudes about premarital sex adolescent and to analyze the relation between the knowledge level of premarital sexual attitudes of adolescent premarital sexual behavior in the female students.Method. Type analytic survey research with cross sectional approach. Total population are 73 students, and total sampleare 73 students.Enclosed questionnaire data collection techniques, data management is done with the help of manual and computerized.Result.The results of the analysis of the level of knowledge most knowledgeable premarital sex either the rate of 49 respondents (67.12%), while the results of the analysis of adolescent attitudes about premarital sex most of the support that is as much as 42 respondents (57.53%).Based on the results table kolmogorov-Smirnov test of significance through a computerized program found that the significance value (p) is 0.993. This indicates that there is no relation between the level of knowledge about adolescent premarital sex with adolescent attitudes about premarital sexual behavior.Recommendation. The results of this study can be expected to support more adolescent to say no to premarital sex and particularly supported by stakeholders such as parents, teachers, religious leaders, and etc